Pengaruh Persepsi Kegunaan dan Persepsi Kemudahan Pengguna Terhadap Keputusan Penggunaan Aplikasi E-Wallet OVO di Indonesia (Studi Kasus pada Pengguna Aplikasi E-Wallet OVO) - Almah Sagita,; Yosi Afandi, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
In Indonesia, OVO is one of the most popular e-wallets due to its diverse range of features that facilitate daily financial transactions. Perceived Usefulness and Perceived Ease of Use are the two main factors that influence a person's decision to use an e-wallet like OVO. The approach used to analyze the perceived usefulness and benefits of a technology is the TAM (Technology Acceptance Model) or technology acceptance model. This study aims to determine and analyze the extent to which perceived usefulness and perceived ease of use affect usage decisions on the OVO e-wallet application. This research is a quantitative study consisting of two independent variables, namely Perceived Usefulness (X1) and Perceived User Ease (X2) and one dependent variable, namely Usage Decisions (Y). The data collection method used is distributing questionnaires to users of the OVO e-wallet application. The data collected was then analyzed using multiple regression analysis to determine how much influence the perceived usefulness and perceived ease of use have on usage decisions. The results of partial and simultaneous hypothesis testing show that perceived usefulness and perceived user convenience have a positive and significant influence on decisions to use the OVO e-wallet application. Research shows that the perceived usefulness variable has a greater contribution than the perceived ease of use. From the results of the study, it can be concluded that perceived usefulness and perceived ease of use have a complementary role in influencing the decision to use the e-wallet application as a whole. This means that users not only consider whether the application is useful, but also the extent to which the application is easy to operate. When both are fulfilled, users will likely decide which to use and continue to utilize e-wallet applications such as OVO in their daily transactional activities.